Ribosomal ribonucleic acid isolated from Salmonella typhimurium: absence of the intact 23S species. - Winkler, M E (1979)
Ribonucleic acid (RNA) isolated by four distinct methods and from a variety of Salmonella typhimurium strains lacked intact 23S ribosomal RNA (rRNA). On sucrose gradients which minimize aggregation, the vast majority of S. typhimurium rRNA sedimented as a 16S peak with a 14S shoulder. RNA from this region of the gradient was resolved into three discrete bands by electrophoresis in formamide. Two very minor S. typhimurium RNA peaks were resolved at 21S and 10S on sucrose gradients, and each peak formed discrete bands in electrophoresis. It is concluded that if S. typhimurium does possess an intact 23S rRNA species, this species is extremely "labile." The absence of isolatable S. typhimurium 23S rRNA possibly reflected in vivo processing of the rRNA before isolation. Under certain conditions, S. typhimurium rRNA formed discrete aggregates which sedimented similarly to intact Escherichia coli 23S rRNA.